Inter-ply angle influence on the out-of-plane compressive response of polyethylene fibre laminates. (July 2018) - O'Masta, M.R.; Russell, B.P.; Ronan, W.
Abstract: Ultra-high molecular weight polyethylene (UHMWPE) fibre reinforced composites find extensive use in impact protection applications. When loaded in out-of-plane (through thickness) compression, UHWMPE laminates composed of a typical cross-ply lay-up (an inter-ply angle of θ = 90°) are known to exhibit fibre tensile rupture via a shear-lag mechanism. This study addresses the effect of inter-ply angle ( θ = 18–90°) on the compressive response of UHMWPE laminates and shows they may fail by this indirect tension mechanism. The shear-lag length increases as θ is reduced, which reduces the compressive strength at small sample sizes. A previous analytical model to predict compressive failure by this mechanism is generalised for laminates with non-orthogonal but constant inter-ply angles. The predictions capture the two key experimental observations which are dependent on inter-ply angle and sample size: the transition from ply shear failure to indirect fibre tensile rupture and the compressive strength.